Power control algorithm for wireless sensor networks based on approximate Unit Delaunay triangulation - Xu, Peng-Fei; Chen, Zhi-Gang; Deng, Xiao-Heng (Tongxin Xuebao, 2013)
A novel geometry structure named AUDT was presented to be as the underlying logical topology of wireless sensor networks, and the transmission range of each sensor was adjusted to the minimum according to its furthest logical neighbor. AUDT would have the desirable features of connectivity, planar, average degree-bounded and t-spanner. The simulation results show that the network delay of AUDT is very close to other similar algorithms, but AUDT performs better than them in terms of the transmission range and the radio interference. Furthermore, the communication cost of distributed constructing AUDT has reached the minimum.